Racism without racists color-blind racism and the persistence of racial inequality in America - Bonilla-Silva, Eduardo 1962- (Rowman & Littlefield, 2018)
Preface to the fifth edition -- The strange enigma of race in contemporary America -- The new racism : the U.S. racial structure since the 1960s -- The central frames of color-blind racism -- The style of color blindness : how to talk nasty about minorities without sounding racist -- "I didn't get that job because of a black man" : color-blind racism's racial stories -- Peeking inside the (white) house of color blindness : the significance of whites' segregation -- Are all whites refined Archie Bunkers? : an examination of white racial progressives -- Are blacks color blind, too? -- E pluribus unum, or the same old perfume in a new bottle? On the future of racial stratification in the United States -- From Obamerica to Trumpamerica : the continuing significance of color-blind racism -- Conclusion: What is to be done? Talking with your about how to fight color -- Blind racism in America
Includes bibliographical references and index
1706
Keywords: Minderheit; Wirtschaft; Rassismus; Diskriminierung; Soziale Situation; Ethnische Beziehungen; Nationale Minderheit; Wirtschaftliche Lage; USA; United States; Race relations; Minorities; Economic conditions; Social conditions; Racism; Minorities / United States / Social conditions; Minorities / United States / Economic conditions; Racism / United States; United States / Race relations